(untitled) (Melayu:Jurnal Antarabangsa Dunia Melayu, 2024)
The study of Sriwijaya literature is gaining more scholarly attention and developing from decade to decade. The purpose of this paper is to historicize a genre of Malay literature that is mixed between prose and poetry as a relic of the campū (“campur” in Malay) genre from the Sriwijaya kingdom. This is a result of two research problems, the first being that some Malay writings narrated since the 14th century were found to cross between prose and poetry, so is this a new phenomenon or a legacy from a previous style of writing? Secondly, is the phenomenon a genre and what is its name? For both of these problems, the approach of studying literature according to the kingdom and the approach of comparative literature has been applied. The first finding discovered that the style of mixing prose and poetry was found in both foreign (e.g. Jātakamālā from India) and local (e.g. Hastadaṇḍaśāstra) works around 687–693 CE, and the second finding discovered that the genre was called campū according to the Sanskrit literary classification for Jātakamālā and others. As a conclusion, the writing style of the Sriwijaya kingdom, which mixed prose and poetry, i.e. campū, was continued in later Malay literature in the kingdoms of Malacca, Johor, Aceh, and beyond. Full text: PDF